Role of topodiagnostic tests in evaluation of facial nerve palsy in head injury - Munjal, Manish; Badyal, Hem Lata; Mehndiratta, Anju; Munjal, Shubham; Bharadwaj, Iti; Kalra, Shivam; Mehta, Arnav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Head injury with temporal bone trauma manifests with facial nerve palsy. The site of lesion can be assessed by various tests. Methods: A retrospective study of 500 cases of head injury was undertaken to study the role of topodiagnostic tests in localising the site of lesion in 48 patients of facial palsy. The study was undertaken by the otology services of Dayanand medical college and hospital, Ludhiana during a period of one year. Cases: 500 cases admitted with head injury were screened. The cases with facial nerve paralysis were then enrolled in the study. Results: In 48 patients of facial palsy, taste sensation was diminished in 67% (21 cases); acoustic reflex absent in 86.8% (33 cases) and Schirmer’s test showed reduced lacrimation in 29.1% (14 cases). Conclusions: The topodiagnostic tests do not always localise the site of lesion in head injury.